Left ventricular endocardial longitudinal dysfunction persists after acute myocarditis with preserved ejection fraction. Issue 12 (12th October 2018) - Di Bella, Gianluca; Carerj, Scipione; Recupero, Antonino; Donato, Rocco; Pugliatti, Pietro; Falanga, Gabriella; Pedri, Stefano; Vizzari, Giampiero; Campisi, Mariapaola; Zito, Concetta; de Gregorio, Cesare
Abstract : Background: The aim of present study was to assess left ventricular (LV) myocardial deformation and changes over time in patients with acute myocarditis (AM) with preserved ejection fraction detected by late gadolinium enhancement (LGE) magnetic resonance imaging. Methods: Thirty‐five male patients with AM diagnoses and preserved systolic function based on cardiac magnetic resonance imaging (MRI) were prospectively enrolled. On admission, echocardiography with measurements of global and segmental longitudinal (LS) strains was performed both at the endocardial (ENDO) and epicardial (EPI) levels. Findings were compared to 25 control subjects. Twenty‐six patients were also monitored over a 22‐month follow‐up (FU group). Results: On admission, global ENDO‐LS was poorer in magnitude in AM (−19.2 ± 3.1) than in controls (−24.0 ± 1.05) ( P  < 0.0001), whereas EPI‐LS was not different (−20.6 ± 3.4 vs −19.7 ± 6 P  = NS). A functional increase in magnitude in both ENDO‐LS (−20.8 ± 5.4, P  = NS) and EPI‐LS (−22.6 ± 4.6, P  = 0.02) was found in FU vs AM patients. Conclusions: The present study demonstrates a steady ENDO‐LS impairment in infarct‐like AM during a 2‐year follow‐up period, despite a preserved LV ejection fraction.